Evaluation of sustainable biopolymer as depressant for iron ore cationic reverse flotation - Oliveira, Flávia Natalino (2014)
The reverse cationic flotation of iron ore is a separation process used in mineralogy to separate iron compounds from others compounds present in iron ore. In this process, the starch is used as depressant and amine as collector. The knowledge of interaction mechanism between the reagents used in the flotation process and iron ore has a fundamental importance to advance iron ore enrichment technology, as well as to the development of new chemicals used in the process. This work is divided into two chapters: i) The first chapter aims to evaluate some characteristics of starch that can influence the flotation process, such as, size of the polymer chain and reducing end group (REG) present in the depressant molecule. It also aims to evaluate, by spectroscopic techniques, the reject and concentrate minerals from flotation tests using dextrin, soluble starch, waxy starch and industrial corn starch as depressant agents. ii) The second chapter aims to develop a new depressant (XMC), extracted from corn fiber residue (CFR), to replace the starch in iron ore flotation process. The results in Chapter 1 showed that short chain depressant results in worse flotation performance. The amount of REG has no effect on flotation performance up to a dextrose equivalent value of 9.2% glucose. Analysis of the DRIFT spectra based on the intensity of the hematite band only showed the concentrate samples contain more hematite than reject samples, as expected. Using Raman spectroscopy analysis, it was not possible to observe any characteristic band of the depressants used, since the Raman was only sensitive to inorganic phase. The studies in Chapter 2 showed the great potential of XMC replacing starch in flotation process, because of the excellent flotation results and the XMC be a sustainable alternative, offering a prime destination to an industrial waste. Besides, it is possible to remove the starch of industrial process partially or totally, preserving it for human and animal food chain.